Analisis Pendapatan Petani Kentang di Desa Candikuning, Kecamatan Baturiti, Kabupaten Tabanan - IDA AYU CANDRA DEWI; I MADE SUDARMA; A.A.A WULANDIRA SAWITRI DJELANTIK (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2016)
AbstractAnalysis Income Farmers Potato in the Village Candikuning, the Subdistrict Baturiti, the District TabananOne of the goals of horticulture development is the increase in farmers' income achieved through increased production and productivity. Horticulture development in Indonesia in the future be driven toward agribusiness system, for example in the village of Tabanan Candikuning which is a village developer horticulture planting all kinds of crops, especially potatoes. To assist in the marketing of potatoes are usually farmers or to cooperate with the relevant agencies where most farmers do partnerships, while there are also other farmers who do not follow the partnership. Under these conditions, this study aims to determine the ratio between the income of farmers who follow a partnership with farmers who do not follow Candikuning partnerships in the village of Tabanan. The data in this study was obtained through interview, observation and documentation, which is then analyzed using qualitative quantitative methods.The results showed that the income of farmers who followed the partnership Rp. 44.326 million while the income of farmers who do not follow the partnership Rp. 17.635 million, with this show that farmers who followed the partnership more beneficial than the farmers who do not follow the partnership. Limitations of quality seeds to farmers to make the production process is hampered because the seeds are supplied directly from outside the area, so if there is a delay in ordering seeds will greatly affect the process production potatoes.